O problema da trissecção - Dellaquila, Allan Jeronymo (2018)
In the history of mathematics some problems had special significance for the influence they exerted in this development. Among these, we mention the classical Greek problems related to construction with a non-graduated ruler and compass. In this work we will discuss these problems, giving special focus to the trisection of the angle. These problems challenged the intellectual power of many mathematicians and intellectuals for a long time, and it was only in the nineteenth century that the impossibility of this construction, using only a non-graduated ruler and compass, was demonstrated. The objective of this work is to present these problems, to discuss their impossibility of resolution and to present, in the special case of the trisection problem, possible resolutions using other instruments. We also present a technique to approach the problem of angle trisection through Origami, which can be used in the classroom.